2018
DOI: 10.1016/j.redox.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acetaminophen-induced liver injury and its implications for therapeutic interventions

Abstract: Acetaminophen (APAP) overdose is the leading cause of drug-induced acute liver failure in many developed countries. Mitochondrial oxidative stress is considered to be the predominant cellular event in APAP-induced liver injury. Accordingly, N-acetyl cysteine, a known scavenger of reactive oxygen species (ROS), is recommended as an effective clinical antidote against APAP-induced acute liver injury (AILI) when it is given at an early phase; however, the narrow therapeutic window limits its use. Hence, the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
325
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 434 publications
(370 citation statements)
references
References 134 publications
(152 reference statements)
1
325
0
4
Order By: Relevance
“…Although it was generally thought that the protective role of autophagy in acetaminophen toxicity was limited to the oxidative damage phase and primarily targeted at damaged mitochondria (Ni et al, , ), our result revealed a sustained activation of autophagy after GCM treatment, which was even observed 12 h post‐acetaminophen challenge, after oxidative stress had already developed. This suggests that a late stage mechanism, such as suppression of ER stress, might be involved in the autophagy‐mediated hepataprotective effect of GCM (Yan et al, ). Although the precise mechanism by which GCM exerts its therapeutic effect against acetaminophen hepatotoxicity in the late phase remains unclear, we observed a better therapeutic effect of GCM against acetaminophen hepatotoxicity compared with NAC, as revealed by the lower effective dose and wider therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was generally thought that the protective role of autophagy in acetaminophen toxicity was limited to the oxidative damage phase and primarily targeted at damaged mitochondria (Ni et al, , ), our result revealed a sustained activation of autophagy after GCM treatment, which was even observed 12 h post‐acetaminophen challenge, after oxidative stress had already developed. This suggests that a late stage mechanism, such as suppression of ER stress, might be involved in the autophagy‐mediated hepataprotective effect of GCM (Yan et al, ). Although the precise mechanism by which GCM exerts its therapeutic effect against acetaminophen hepatotoxicity in the late phase remains unclear, we observed a better therapeutic effect of GCM against acetaminophen hepatotoxicity compared with NAC, as revealed by the lower effective dose and wider therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…So, glucose‐6‐phosphate dehydrogenase and pentose phosphate pathways are activated in order to maintain normal NADPH level in hepatocytes. These processes lead to glycogenolysis or, in other words, depletion of glycogen in the liver cell cytoplasm (Gusarov & Nudler, ; Yan, Huo, Yin, & Hu, ). In this study, staining specific for glycogen revealed that APAP administration led to significant consuming of glycogen but to a lesser extent in animals pretreated with PYC.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism leads to in vivo 34: 569-582 (2020) 576 mitochondrial oxidative stress, increased mitochondrial membrane permeability and hepatic cell death (45). Mitochondrial oxidative stress is considered to be the main cellular dysfunction in APAP-induced liver injury (46). In our study, the levels of oxidative stress molecules (NOx and MDA) significantly increased after APAP administration (250 mg/kg) (Table II, Figures 4 and 5).…”
Section: Liposomal Curcumin Effect On Hepatic Function and Oxidative mentioning
confidence: 53%
“…The hepatoprotective effect of LCC could be linked to its already proven inhibitory effect on iNOS activity (52) and MDA production (51) as well as its ability to maintain the thiol pool (53) and to improve catalase production (54). In addition to mitochondrial oxidative stress, many other cellular processes, including inflammation, microcirculatory dysfunction and extracellular matrix degradation, have been shown to be involved in the pathogenesis of APAP-induced liver injury (46,55).…”
Section: Liposomal Curcumin Effect On Hepatic Function and Oxidative mentioning
confidence: 99%